Balanced Nutrition Knowledge and Eating Patterns with Nutritional Status of Adolescents - Hanny Tri Anysha Pinem; Betty Yosephin Simanjuntak; Ahmad Rizal (Sarana Ilmu Indonesia (Salnesia), 2026)
Adolescents were a vulnerable age group to nutritional problems due to rapid physical growth and development. These problems could be prevented through the implementation of a balanced diet supported by adequate nutritional knowledge, as the level of knowledge influenced food choices and the fulfillment of nutritional needs. This study aimed to analyze the relationship between balanced nutrition knowledge, dietary patterns, and the nutritional status of students at SMA Negeri 7 Bengkulu City. This study used a quantitative method with a cross-sectional design involving 60 tenth-grade students who were selected through a cluster random sampling technique. The research instruments included informed consent, a balanced nutrition knowledge questionnaire, the Diet Quality Questionnaire (DQQ), and measurements of body weight and height to determine body mass index-for-age (BMI-for-age). The results showed that most students had poor nutritional knowledge (58.3%), unhealthy dietary patterns (51.7%), and non-normal nutritional status (46.7%). The Chi-square test indicated a significant relationship between nutritional knowledge and nutritional status (p = 0.029), as well as between dietary patterns and nutritional status (p = 0.037). These findings suggested that improving adolescents' nutritional status required interventions that not only enhanced knowledge but also promoted changes in eating behavior and supported a healthy food environment.